An Existence Result for Second-Order Impulsive Differential Equations with Nonlocal Conditions - Meili Li; Haiqiang Liu (Discrete Dynamics in Nature and Society)
The Leray-Schauder alternative is used to investigate the existence of solutions for second-order impulsive differential equations with nonlocal conditions in Banach spaces. The results improve some recent results.